Smart Microgrids - Nayeripour, Majid; Waffenschmidt, Eberhard; Kheshti, Mostafa (IntechOpen, 2018)
Public support and feed-in tariff as a nonvariable compensation for the electric power production of energy have suppressed the risky investment of distributed generators (DGs) in smart distribution systems (SDSs). Although the using renewable energy technologies and the incorporation of plug-in DGs into SDS may have positive effects on congestion management, power loss reduction, and sustainability, they may create some difficulties relating to manage the system optimally by considering the intermittency of renewable resources in power production and uncertainties. Many researches have been carried out to deliver the high-quality power to the end-users with acceptable reliability. This book aims to present the recent materials related to the smart microgrids and the management of intermittent renewable energy sources that organized into seven chapters.